Compete by meeting unmet needs how Zipcar rethought the car rental business - Champy, James 1942- (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Inspire!: why customers come back (ISBN: 9780131361881) by Jim Champy. Today's most powerful value proposition: combining ease of use with cost savings! How Zipcar has done it--with lessons you can apply in your own business"--Resource description page.
Keywords: Zipcar (Firm); Automobile leasing and renting -- United States; Success in business; Branding (Marketing); Automobiles; Location; États-Unis; Succès dans les affaires; Stratégie de marque; branding; Automobile leasing and renting; United States